2012
DOI: 10.1080/14616734.2012.706394
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment representations predict cortisol and oxytocin responses to stress

Abstract: There are many factors contributing to individual variations in the response to stressful experiences. The present study evaluated the patterns of stress responses according to attachment representations in 28 adults from a community sample, plus 46 subjects expected to be particularly sensitive to stress, having been exposed during childhood and/or adolescence to traumatizing events such as abuse or potentially lethal illnesses. Subjects were given the Adult Attachment Interview, which provides attachment cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
85
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 88 publications
2
85
1
1
Order By: Relevance
“…Securely attached mothers have an increase in oxytocin when playing with their infants while insecurely attached mothers' oxytocin levels actually decrease with play (Strathearn, Fonagy, Amico, & Montague, 2009). Furthermore, secure attachment was correlated with higher oxytocin levels and decreased subjective stress during an acutely stressful situation (Pierrehumbert, Torrisi, Ansermet, Borghini, & Halfon, 2012). Hence, it appears that oxytocin and secure attachment may regulate the stress system.…”
Section: Oxytocin: Attachment and Synchronicitymentioning
confidence: 92%
See 3 more Smart Citations
“…Securely attached mothers have an increase in oxytocin when playing with their infants while insecurely attached mothers' oxytocin levels actually decrease with play (Strathearn, Fonagy, Amico, & Montague, 2009). Furthermore, secure attachment was correlated with higher oxytocin levels and decreased subjective stress during an acutely stressful situation (Pierrehumbert, Torrisi, Ansermet, Borghini, & Halfon, 2012). Hence, it appears that oxytocin and secure attachment may regulate the stress system.…”
Section: Oxytocin: Attachment and Synchronicitymentioning
confidence: 92%
“…Cortisol increases plasma oxytocin levels, hence this serves as a negative feedback system where stress increases cortisol, which then increases oxytocin, which then decreases cortisol. In individuals who are securely attached, oxytocin levels increase in response to stress (Pierrehumbert, Torrisi, Ansermet, Borghini, & Halfon, 2012). Given that women with a history of child abuse have lower oxytocin levels in general (Heim et al, 2009), it is possible that insecurely attached individuals do not have this inhibitory process in place, allowing the stress response to escalate to higher levels.…”
Section: The Stress Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have reported insecure dismissing attachment style to predict enhanced cortisol reactivity (Pierrehumbert et al, 2012;RifkinGraboi, 2008) whereas secure and dismissive attachment styles have been reported as similar elsewhere (Kidd et al, 2011). Further studies show no relationship between cortisol responding to a stressor and attachment style (e.g.…”
mentioning
confidence: 96%